Economic Sustainability and Fishery Business Development of Small Scale Lift Net Raft in Namar Village, Southeast Maluku District, Maluku Province - Picaulima, Simon Marsholl; Ngangun, Tati Atia; Labetubun, Welem; Elwuar, Mifta Khul; Farneubun, Alexander Vigo (Faculty of Fisheries and Marine, Universitas Riau, 2022)
The lift net raft fisheries business is a production activity carried out by small fishermen for economic purposes, but the sustainability and development of this business is strongly influenced by economic, internal and external factors. The research was conducted from January 2022 to July 2022 in Ohoi Namar, Southeast Maluku District. The purpose of this research is to determine the feasibility of a fishery business and the right business development strategy. Primary and secondary data were collected using a survey method, with interview, questionnaire and observation, the data analyzed by business feasibility analysis and SWOT. The results of the study show that the lift net raft fishries business is feasible to continue because it has a NPV value of Rp. 548,200,783, IRR = 102%, Net B/C = 5.0, and PP = 2.0. The business development strategy consists of the SO strategy which includes increasing fleet capacity, improving the quality of cath, optimizing secondary cath when season transition 1 and 2. The WO strategy is to improve lighting technology, expand marketing networks, optimize information technology to expand market access, improve the quality of education for ABK owners and fishermen. ST' strategy includes implementing environmentally friendly fishing technology and health protocols in every aspect of the business. WT' strategy is cooperation with KKP in coastal and ocean management, efficiency and effectiveness of production costs and fishing time.